2016
DOI: 10.1631/jzus.b1500266
|View full text |Cite
|
Sign up to set email alerts
|

Cholangiocarcinoma-derived exosomes inhibit the antitumor activity of cytokine-induced killer cells by down-regulating the secretion of tumor necrosis factor-α and perforin

Abstract: Abstract:Objective: The aim of our study is to observe the impact of cholangiocarcinoma-derived exosomes on the antitumor activities of cytokine-induced killer (CIK) cells and then demonstrate the appropriate mechanism. Methods: Tumor-derived exosomes (TEXs), which are derived from RBE cells (human cholangiocarcinoma line), were collected by ultracentrifugation. CIK cells induced from peripheral blood were stimulated by TEXs. Fluorescence-activated cell sorting (FACS) was performed to determine the phenotypes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…Since CD3 + T lymphocytes are the main components of CIK cells and perforin is important in the antitumor effects of CIK cells (17), an immunohistochemical study was further performed on the excised tumor tissue with anti-CD3 and anti-perforin antibodies. The results revealed that there was significantly more accumulation of CD3 + T lymphocytes and perforin in tumor tissue treated with CIK cells plus NaHCO 3 compared with tumor tissue treated with CIK cells alone (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Since CD3 + T lymphocytes are the main components of CIK cells and perforin is important in the antitumor effects of CIK cells (17), an immunohistochemical study was further performed on the excised tumor tissue with anti-CD3 and anti-perforin antibodies. The results revealed that there was significantly more accumulation of CD3 + T lymphocytes and perforin in tumor tissue treated with CIK cells plus NaHCO 3 compared with tumor tissue treated with CIK cells alone (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A study of co-culture system between CAFs and iCCA cells demonstrated that miR-195, carried by CAF-derived exosomes, could inhibit tumor proliferation and invasion in vitro [101]. Another study conducted by Chen et al demonstrated that CCA-derived exosomes support iCCA cells to escape the attack of the immune system by preventing cytokine-induced killer (CIK) cells from producing molecules with anticancer effect, such as tumor necrosis factor (TNF)-α and perforin [102]. Hence, the in vitro study of exosomes-TME interactions may be important for the development of new therapeutic approaches.…”
Section: D Models: Cell Lines and Primary Cell Culturesmentioning
confidence: 99%
“…The proteomics analysis of normal bile duct cells and CCA cells confirmed the differences between these two cell types, and these differences need to be further studied. Moreover, exosomes from another CCA cell line (RBE) could inhibit the antitumor activity of cytokine-induced killer (CIK) cells by downregulating the populations of CD3 + , CD8 + , Circ-0000284 HuCCT1 and RBE Gene LY6E Enhancing the migration, invasion and proliferation of CCA cells [86] NK (CD56 + ) and CD3 + CD56 + cells and secreting TNF-α and perforin [65]. According to some research, mutations in the IDH1 gene is common in a variety of tumors, including iCCA [66,67].…”
Section: The Function Of Evs In Tumor Microenvironmentmentioning
confidence: 99%